Empirical Learner Language and the Levels of the Common European Framework of Reference. (12th January 2017) - Wisniewski, Katrin
Abstract : The Common European Framework of Reference (CEFR) is the most widespread reference tool for linking language tests, curricula, and national educational standards to levels of foreign language proficiency in Europe. In spite of this, little is known about how the CEFR levels (A1–C2) relate to empirical learner language(s). This article sums up recent trends to meet the need of empirical CEFR level research, where learner corpus‐based analyses play an increasing role. A first focus of the article is on studies that aim at illustrating CEFR levels by analyzing rated learner texts ("criterial features"). Furthermore, research that tries to disentangle the empirical validity of the CEFR scales by operationalizing its descriptors is presented. Before concluding with an outline of the most urgent research needs, potentials, and boundaries of interdisciplinary work between the fields of language testing and assessment, second language acquisition, and learner corpus research are discussed.